STRUCTURAL MODEL OF THE PERSONNEL CORE OF A MEDICAL INSTITUTION BASED ON A SEGMENT APPROACH - Zadnieprovska, Ganna (Public Management and Policy, 2025)
The article considers the current problem of forming and managing the core personnel of medical institutions based on a segment approach. The main directions of the transformation of the personnel core are investigated, in particular, changes in its role structure, development of the competences of participants, and creation of a favorable environment for its functioning. A model of the formation of the personnel core is proposed, which provides for a two-way influence: directly on the core and on the surrounding environment. The cycle of the formation of the personnel core is highlighted, which includes the stages of creation, development, transformation, and maintenance. Special attention is paid to the reserve of the personnel core, which ensures its stability and renewal. Methodological principles of segmentation of the personnel core include: 1. Segmentation methodology – a comprehensive approach that combines functional-competence and segment methods. The stages of allocation of structural elements of the core are determined from the institution’s strategy to the definition of functions, roles, and competencies. 2. Segmentation technology – a detailed scheme that includes 10 stages (from strategy refinement to assessment of the contribution of structural elements). Methods for implementing each stage are proposed, in particular involving project groups. 3. Segmentation principles – target orientation, periodicity, differentiation of personnel work, confidentiality, reliability of criteria, voluntary participation. 4. Taking into account the characteristics of medical institutions – administrative-bureaucratic management style, weak corporate culture, lack of resources. The structural model of the personnel core is built based on a combination of objective (position category, qualifications, experience) and subjective (role affiliation, motivation, participation in the strategy) criteria. A methodology for identifying participants in the personnel core is proposed, which takes into account their professional status, performance results, and competence. The study has practical value for managers of medical institutions, HR specialists, and researchers in the field of personnel management.